Inovasi Briket Daun Kering: Pelatihan Kewirausahaan Berwawasan Lingkungan untuk Masyarakat Desa Kaliwungu, Kecamatan Jombang - Chusnul Rofiah; Nuri Purwanto; Erminati Pancaningrum (Institut Teknologi dan Bisnis Semarang, 2025)
The problem of organic waste, especially dry leaves, is one of the environmental challenges that has not been optimally resolved in Indonesia. Kaliwungu Village, Jombang District, is one of the areas that has high potential for dry leaf waste, but has not been utilized economically. Most of this waste is simply burned, causing air pollution and carbon emissions. This community service program aims to empower environmental cadres and PKK cadres through training in making briquettes from dry leaves, which not only provides environmental solutions but also opens up business opportunities based on social entrepreneurship. The training was carried out for three days involving 30 participants. Activities included socialization, technical training, business simulations, and evaluation of results. The results showed a significant increase in participant understanding, with an average pretest score of 40% increasing to 85% in the posttest. As an output, participants succeeded in producing 300 briquettes that met alternative fuel quality standards. In addition, most participants expressed their readiness to start a briquette business independently or in groups. This program has a positive impact on social, economic, and environmental aspects, in line with the principles of sustainable development and the Sustainable Development Goals (SDGs) agenda, especially point 8 (Decent Work and Economic Growth) and point 12 (Responsible Consumption and Production). With continued assistance and collaboration with strategic partners, it is hoped that this program will be able to create a sustainable small business ecosystem based on the environment and provide wider benefits for the people of Kaliwungu Village.